Little kids first big book of who - Esbaum, Jill (Washington, D.C. : National Geographic Society, 2015)
"Read amazing stories about Martin Luther King, Jr., Amelia Earhart, Mohandas Gandhi, and many other fascinating and inspiring people from all over the world. These colorful and kid-friendly pages introduce younger readers to more than 50 people and their interesting lives"--Page 4 of cover.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references (page 125) and index.
Description based on print version record.
Keywords: Biography -- Juvenile literature; Electronic books- OSLIS; Picture books for children; Electronic books